The assess of the ecological functioning of urban ecosystems of Białystok using the methods of monitoring with lichens - Matwiejuk, Anna (Ecological Questions, 2013)
The paper attempts to assess the ecological functioning of urban ecosystems of Białystok using the bioindication methods - lichen response to gaseous pollutants originating mainly from the transport and combustion of fossil fuels in power plants and household furnaces. To assess the degree of air pollution by sulfur dioxide (SO2) in the area of the city of Białystok, three lichen-indicative methods were used: 1. floristic approach, 2. method of participation of morphological forms, and 3. chemical analytical method involving the analysis of the chemical composition of trace elements (Pb, Ni, Cu, Zn, Fe) in the thallus of Hypogymnia physodes